A novel G protein‐biased agonist at the μ opioid receptor induces substantial receptor desensitisation through G protein‐coupled receptor kinase. (27th December 2020) - Groom, Sam; Blum, Nina K.; Conibear, Alexandra E.; Disney, Alexander; Hill, Rob; Husbands, Stephen M.; Li, Yangmei; Toll, Lawrence; Kliewer, Andrea; Schulz, Stefan; Henderson, Graeme; Kelly, Eamonn; et al.
Abstract : Background and Purpose: G protein‐biased μ opioid receptor agonists have the potential to induce less receptor desensitisation and tolerance than balanced opioids. Here, we investigated if the cyclic endomorphin analogue Tyr‐c[D‐Lys‐Phe‐Tyr‐Gly] (Compound 1) is a G protein‐biased μ agonist and characterised its ability to induce rapid receptor desensitisation in mammalian neurones. Experimental Approach: The signalling and trafficking properties of opioids were characterised using bioluminescence resonance energy transfer assays, enzyme‐linked immunosorbent assay and phosphosite‐specific immunoblotting in human embryonic kidney 293 cells. Desensitisation of opioid‐induced currents were studied in rat locus coeruleus neurones using whole‐cell patch‐clamp electrophysiology. The mechanism of Compound 1‐induced μ receptor desensitisation was probed using kinase inhibitors. Key Results: Compound 1 has similar intrinsic activity for G protein signalling as morphine. As predicted for a G protein‐biased μ agonist, Compound 1 induced minimal agonist‐induced internalisation and phosphorylation at intracellular μ receptor serine/threonine residues known to be involved in G protein‐coupled receptor kinase (GRK)‐mediated desensitisation. However, Compound 1 induced robust rapid μ receptor desensitisation in locus coeruleus neurons, to a greater degree than morphine. The extent of Compound 1‐induced desensitisation was unaffected by activation or inhibition of protein kinase C (PKC) but was significantly reduced by inhibition of GRK. Conclusion and Implications: Compound 1 is a novel G protein‐biased μ agonist that induces substantial rapid receptor desensitisation in mammalian neurons. Surprisingly, Compound 1‐induced desensitisation was demonstrated to be GRK dependent despite its G protein bias. Our findings refute the assumption that G protein‐biased agonists will evade receptor desensitisation and tolerance. LINKED ARTICLES: This article is part of a themed issue on Advances in Opioid Pharmacology at the Time of the Opioid Epidemic. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v180.7/issuetoc Abstract :